Urban Real Estate Markets: A Catalyst for Economic Growth and Development - The 14th African Real Estate Society Conference 2014
DOI: 10.15396/afres2014_104
|View full text |Cite
|
Sign up to set email alerts
|

Valuers Enlistment and Fees Standardization Practices in Nigeria Banking Industry: Implication for Real Estate Profession

Abstract: M SC. (EST. MGT.), M. SC (GEN MGT) FRANCIS OKPALEKE 2 M.SC (EST. MGT) MPM, ANIVS, RSV DE OMOROGIEVA, 3 HND, DIP (EST. MGT) ANIVS, RSV and JANE I EMEGHE 4 B.SC M SC. (EST. MGT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the same vein, Sirmans and Turnbull (1997) found that because of competition brokerage rate is determined by the housing market behaviour and broker cost conditions instead of the general belief that brokerage fee is fixed. The only study relating to this phenomenon among valuation literature, to our knowledge, is the study by Adjekophori et al (2014) which focusses on the practice of valuers enlistment and fees standardisation by financial institutions in Nigeria. While Adjekophori et al (2014) made an appreciable contribution to the discussion, the study did not provide detail insight into the pricing system existing for valuation practice.…”
Section: Pricing Policies Of Service Organisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same vein, Sirmans and Turnbull (1997) found that because of competition brokerage rate is determined by the housing market behaviour and broker cost conditions instead of the general belief that brokerage fee is fixed. The only study relating to this phenomenon among valuation literature, to our knowledge, is the study by Adjekophori et al (2014) which focusses on the practice of valuers enlistment and fees standardisation by financial institutions in Nigeria. While Adjekophori et al (2014) made an appreciable contribution to the discussion, the study did not provide detail insight into the pricing system existing for valuation practice.…”
Section: Pricing Policies Of Service Organisationsmentioning
confidence: 99%
“…The only study relating to this phenomenon among valuation literature, to our knowledge, is the study by Adjekophori et al (2014) which focusses on the practice of valuers enlistment and fees standardisation by financial institutions in Nigeria. While Adjekophori et al (2014) made an appreciable contribution to the discussion, the study did not provide detail insight into the pricing system existing for valuation practice. This limitation could be attributed to the positivist paradigm and quantitative methodology approach employed by the authors who did not provide for deep probing into personal experiences and views of valuers on issues associated with the phenomenon.…”
Section: Pricing Policies Of Service Organisationsmentioning
confidence: 99%